2006
DOI: 10.1094/phyto-96-1188
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan Oligomers and Copper Sulfate Induce Grapevine Defense Reactions and Resistance to Gray Mold and Downy Mildew

Abstract: Chitosan (CHN), a deacetylated derivative of chitin, was shown to be efficient in promoting plant defense reactions. CHN oligomers of different molecular weight (MW) and degree of acetylation (DA) triggered an accumulation of phytoalexins, trans- and cis-resveratrol and their derivatives epsilon-viniferin and piceid, in grapevine leaves. Highest phytoalexin production was achieved within 48 h of incubation with CHN at 200 mug/ml with an MW of 1,500 and a DA of 20% (CHN1.5/20), while oligomers with greater MW w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
155
0
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 220 publications
(181 citation statements)
references
References 52 publications
7
155
0
3
Order By: Relevance
“…These data also confirm earlier studies which showed that saccharin treatment primed CAD activity in barley against subsequent challenge with powdery mildew [65]. As for Chiosan, in recent years, the importance of chitosaccha-rides as plant growth promoting and disease control agents has been emphasized [67,68]. CHN (β-1-4 linked N-gluco-samine) has been shown to induce defense responses in different plants [69,70].…”
Section: Integrated Fungicidal Alternatives and Yeast (S Cerevisiae)supporting
confidence: 87%
See 1 more Smart Citation
“…These data also confirm earlier studies which showed that saccharin treatment primed CAD activity in barley against subsequent challenge with powdery mildew [65]. As for Chiosan, in recent years, the importance of chitosaccha-rides as plant growth promoting and disease control agents has been emphasized [67,68]. CHN (β-1-4 linked N-gluco-samine) has been shown to induce defense responses in different plants [69,70].…”
Section: Integrated Fungicidal Alternatives and Yeast (S Cerevisiae)supporting
confidence: 87%
“…CHN (β-1-4 linked N-gluco-samine) has been shown to induce defense responses in different plants [69,70]. Chitosan oligomers was found to induce defense responses in grapevine leaves, as evidenced by an accumulation of stilbene phytoalexins, trans-and cis-resveratrol, ε-viniferins, and piceids, and a stimulation of chitinase and β-1,3-glucanase activities [68]. They added that the combination of Chitosan and CuSO 4 increased phytoalexin production.…”
Section: Integrated Fungicidal Alternatives and Yeast (S Cerevisiae)mentioning
confidence: 99%
“…Soil amendment with chitosan has repeatedly been shown to control fungal diseases in numerous crops, especially Fusarium wilts [31][32][33] and grey mould [34,35]. It is also of note that these studies show chitosan to be fungistatic against both biotrophic and necrotrophic pathogens.…”
Section: Effectiveness Of Chitin-based Treatments Against Fungal Pathmentioning
confidence: 95%
“…These features, together with their biocompatibility, biodegradability, and nontoxicity make them as interesting biopolymers for application in medicine, cosmetic, biotechnology, food and agriculture, etc. Oligochitosan is effective at eliciting plant innate immunity against disease in plant such as tomato [6], grapevine [7], etc. Therefore, Yin et al (2010) supposed oligochitosan as a plant vaccine that is similar with general animal vaccine [8].…”
Section: Introductionmentioning
confidence: 99%